Na(+)–Ca(2+) Exchanger, Leak K(+) Channel and Hyperpolarization‐Activated Cyclic Nucleotide‐Gated Channel Comediate the Histamine‐Induced Excitation on Rat Inferior Vestibular Nucleus Neurons - Yu, Lei (CNS Neurosci Ther, 2015)
AIMS: Antihistaminergic drugs have traditionally been used to treat vestibular disorders in the clinic. As a potential central target for antihistaminergic drugs, the inferior vestibular nucleus (IVN) is the largest subnucleus of the central vestibular nuclear complex and is considered responsible for vestibular‐autonomic responses and integration of vestibular, cerebellar, and multisensory signals. However, the role of histamine on the IVN, particularly the underlying mechanisms, is still not clear. METHODS: Using whole‐cell patch‐clamp recordings on rat brain slices, histamine‐induced effect on IVN neurons and the underlying receptor and ionic mechanisms were investigated. RESULTS: We found that histamine remarkably depolarized both spontaneous firing neurons and silent neurons in IVN via both histamine H1 and histamine H2 receptors. Furthermore, Na(+)–Ca(2+) exchangers (NCXs) and background leak K(+) channels linked to H1 receptors and hyperpolarization‐activated cyclic nucleotide‐gated (HCN) channels coupled to H2 receptors comediate the histamine‐induced depolarization on IVN neurons. CONCLUSION: These results demonstrate the multiple ionic mechanisms underlying the excitatory modulation of histamine/central histaminergic system on IVN neurons and the related vestibular reflexes and functions. The findings also suggest potential targets for the treatment of vestibular disorders in the clinic, at the level of ionic channels in central vestibular nuclei.